Analisis Kemampuan Numerasi Siswa SMP dalam Menyelesaikan Soal Asesmen Kompetensi Minimum (AKM) ditinjau dari Adversity Quotient (AQ) - Setiaji, Heru Agni; Nuha, Muhammad Azmi; Nuron, Waskita Ahmad (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dayanu Ikhsanuddin, 2024)
This research aims to determine the effect of Adversity Questions (AQ) on junior high school students' numeracy abilities in solving Minimum Competency Assessment (AKM) questions and analysis of students' numeracy abilities in terms of their Adversity Quotient. The research was carried out at SMP Negeri 4 Semarang with a sample size of 157 class VIII students. This research is a combination research (mix method) type The Explanatory Sequential Design. The research results show that there is a significant influence between AQ on junior high school students' numeracy abilities in solving AKM questions. This is proven by testing two variables which shows that the significance value of the AQ variable is less than α with a value of 0.000 (0.000 ≤ 0.05). The simple linear regression equation obtained is Ŷ = 20.731 + 0.318X. This states that for every additional unit of AQ value (X), the student's numeracy ability value (Y) increases by 0.318. The coefficient of determination obtained was 0.342, which means that the influence of AQ on students' numeracy abilities was 34.2%, while survival was 65.8% influenced by other variables. The numeracy abilities of students in solving AKM questions in each AQ category obtained the following results: 1) The numeracy abilities of students in the Quitter category only reached the cognitive understanding process well, but the standard cognitive process was not optimal, so Quitter students did not reach the on cognitive reasoning processes. 2) The numeracy abilities of students in the Camper category have reached the understanding process well, as well as the cognitive process of application, but the reasoning process has not been maximized. 3) The numeracy abilities of students in the Climber category in the understanding, application and reasoning process are maximal.